The effect of fucoxanthin on the development of CCl4-induced liver fibrosis - V. N. Slautin; D. Yu. Grebnev; I. Yu. Maklakova; S. V. Sazonov; I. V. Gavrilov; E. I. Gavrilova (Фундаментальная и клиническая медицина, 2023)
Background. According to current concepts regarding hepatic fibrosis, myofibroblast differentiation from stellate cells, regulated by transforming growth factor-β (TGF-β), is a key step in its pathogenesis. Hence, inhibition of TGF-β-dependent activation of hepatic stellate cells has been suggested as a promising strategy for preventing the disease development.Aim. To explore whether the administration of fucoxanthin at a dose of 30 mg/kg is efficient in suppressing hepatic fibrosis.Materials and Methods. The experiments were carried out on 30 outbred ICR/CD1 mice which have been divided into three groups: intact animals, animals with untreated hepatic fibrosis which has been induced by intraperitoneal injections of CCl4 (2 μl/g, 6 weeks, twice per week), and animals which received fucoxanthin per os (30 mg/kg daily for 5 weeks) after inducing hepatic fibrosis as described above. Histological examination was performed by Sirius Red staining using the METAVIR fibrosis and activity score. Immunohistochemical analysis was performed by quantitation of α-SMA-positive myofibroblasts, CD45-positive leukocytes, and TIMP-1-positive regions. Further, we quantified TGF-β in liver homogenate as well as interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the serum by means of enzyme-linked immunosorbent assay. An assessment of liver function was conducted by measuring serum alanine aminotransferase, aspartate aminotransferase, and albumin levels.Results. Fucoxanthin decreased the number of myofibroblasts and leukocytes, the volume of connective tissue and TIMP-1-positive regions, and the level of TGF-β in the liver homogenate, altogether indicative of ameliorated hepatic fibrosis. In accord, treatment with fucoxanthin reduced serum IL-1β, TNF-α, alanine aminotransferase and aspartate aminotransferase, and increased serum albumin.Conclusion. Treatment with fucoxanthin at a dose of 30 mg/kg has an antifibrotic effect and diminishes liver fibrosis.